Pengaruh Rating dan Review Melalui Google Reviews Terhadap Keputusan Pembelian Konsumen di Arch Alley Batam - Muhammad Alfiza; Dailami .; Natal Olotua Sipayung; Rezki Alhamdi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study is motivated by the growing consumer behavior in food and beverage spending and the increasing role of Google Maps as an e-WOM platform influencing purchasing decisions. This research aims to examine the effect of Google Maps ratings and reviews on consumers’ purchasing decisions at Arch Alley Restaurant Batam. A quantitative approach with a causal associative design was employed, involving 111 respondents selected through purposive sampling. The research instrument was tested using validity and reliability tests, followed by classical assumption tests including normality, multicollinearity, and heteroscedasticity. Data were analyzed using multiple linear regression, supported by t-tests to assess partial effects and an F-test to evaluate simultaneous influence. The findings indicate that both rating and review significantly and positively affect purchasing decisions, with rating being the most dominant variable. Overall, the results highlight the essential role of digital reputation in shaping consumer decisions and strengthening customer loyalty.